Pancasila Buddhist learning and ethical behaviour students’ at Xaverius 2 Pahoman junior high school in Bandar Lampung - Yandana Yandana; Dedi Kundana; Taridi Taridi (International Journal of Science and Applied Science: Conference Series, 2025)
This study aims to determine the effect of Buddhist Pañcasīla learning on the ethical behaviour of students at Xaverius 2 Pahoman Junior High School, Bandar Lampung. The background of this study is the identification of a number of problems, such as the lack of ethical behaviour exhibited by students in their daily lives, their limited understanding of the values contained in Buddhist Pañcasīla, low awareness of the importance of social responsibility, and minimal self-reflection skills, which should be part of student character development. This study used a quantitative approach with a survey method as the data collection technique. Data were obtained by distributing questionnaires to predetermined respondents. The sample in this study consisted of 66 students, including 28 seventh-grade students and 38 eighth-grade students in the 2024/2025 academic year. The results showed that Buddhist Pañcasīla learning had a significant and positive effect on improving students' ethical behaviour. The more intensively this material was delivered in the learning process, the more noticeable the improvement in students' ethical attitudes and actions, both at school and at home. Based on the results of linear regression analysis, a contribution of 78.8% was obtained, with the equation Y = 6.247 + 0.062X, while the remaining 21.2% was influenced by other factors. Thus, Buddhist Pañcasīla learning plays a major role in shaping students' character and ethical behaviour in a better and more responsible direction.